Anaphylaxis - Kundan Mittal; Neeraj Yadav; Utkarsh Sharma; Jayant Vagha (Wolters Kluwer Medknow Publications, 2019)
Anaphylaxis is common medical emergency seen in children. Out of various offending agents' food and drugs are common etiological factors associated with anaphylaxis. It can be immunogenic, non-immunogenic or idiopathic in nature. Diagnosis is mainly clinical and cutaneous and respiratory symptoms are common. Treatment is mainly intramuscular epinephrine and supportive.